Carcass Characteristics And Physiological Status Of Nutrients Carcass Characteristics And Physiological Status Of Nutrients Including Heavy Metal And Pesticide Residues In Selected Beef esticide Residues In Selected Beef Wholesale Cuts Of Indian Zebu Cat - Chakraborty, A.; Biswas, S.; Chakraborty, R.; (Chakraborty), A. Dhargupta; (Chakraborty), A. Dhargupta; Majumder, D. (Journal of Meat Science, 2022)
A study was carried out to assess the carcass characteristics, proximate composition, fatty acid profile, essential macro and micro-elements as well as the levels of some heavy metals and pesticide residues in some wholesale cutup parts (round, loin, flank and chuck) of pasture-fed Indian zebu cattle after collecting samples from the Tangra slaughter house, Kolkata, India. The carcass characters, weight of the wholesale cuts and plucks were having agreement with the standard values. Significant (P<0.05) differences were observed in terms of moisture, crude protein, total lipid, energy, different fatty acids and cholesterol among the four different cut-up parts. The pH, Water Holding Capacity (WHC), fibre diameter and sarcomere length also varied significantly (P<0.05) among them. The concentration of Iron (Fe) and Sodium (Na) was highest in round, Calcium (Ca) was highest in flank whereas the Potassium (K), Magnesium (Mg), Zinc (Zn), Selenium (Se) and Phosphorus (P) was found to be highest in chuck. The differences were also significant (P<0.05). Regarding the heavy metals, i.e. Lead (Pb), Arsenic (As), Cadmium (Cd) and Cromium (Cr) and pesticide residues (DDT and Endosulfan), all the values was highest in loin part and almost lowest in round. The amount of Aldrin was found to be below the detectable limit in all the four cut-up parts.